2007
DOI: 10.1021/ef060452i
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Pt/MgO/CNT Hybrid Catalysts and Their Electrocatalytic Properties for Ethanol Electrooxidation

Abstract: The micrograph and elemental compositions of Pt/MgO/CNT catalysts were characterized by scanning electron microscopy and energy-dispersive X-ray spectroscopy, respectively. The electrocatalytic properties of the Pt/ MgO/CNT catalyst for ethanol oxidation have been investigated by cyclic voltammetry in 1.0 mol L -1 CH 3 -CH 2 OH and 1.0 mol L -1 KOH aqueous solution. The effect of the content of MgO on the electrocatalytic activity of the Pt/MgO/CNT catalyst was also investigated. Under the same Pt loading mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…This behavior is different from that of Pt-based catalysts, which are easily poisoned by the oxidation products of ethanol, such as CO and other intermediates. [15] A current density as high as about 3 mAcm À2 can be achieved when the ethanol concentration is 2 m. It is also noticeable that the EER potential on the [(HOC 2 H 4 ) 2 dtoaCu] catalyst is lower than some of the reported EER potential values on the Pt-based catalysts in acidic media, such as Pt-Sn, [16] Pt/MWNT, [17] and Pt nanocrystals. [18] The effect of the potential sweep rate on the behavior of ethanol oxidation was also investigated.…”
Section: Angewandte Chemiementioning
confidence: 96%
“…This behavior is different from that of Pt-based catalysts, which are easily poisoned by the oxidation products of ethanol, such as CO and other intermediates. [15] A current density as high as about 3 mAcm À2 can be achieved when the ethanol concentration is 2 m. It is also noticeable that the EER potential on the [(HOC 2 H 4 ) 2 dtoaCu] catalyst is lower than some of the reported EER potential values on the Pt-based catalysts in acidic media, such as Pt-Sn, [16] Pt/MWNT, [17] and Pt nanocrystals. [18] The effect of the potential sweep rate on the behavior of ethanol oxidation was also investigated.…”
Section: Angewandte Chemiementioning
confidence: 96%
“…The resulting amino-functionalized QDs then reacted with the carboxylic groups of the acid-treated CNTs to form amide bonds. Metal oxides can be attached to the carboxyl groups without any linking agent due to their hydrophilic nature, as recently demonstrated for MnO 2 [111], MgO [112], and TiO 2 [113]. However, the authors observed only weak interactions between the oxides and the acidterminated CNTs, resulting in rather nonuniform distributions of the nanoparticles.…”
Section: Covalent Interactionsmentioning
confidence: 81%
“…As displayed in Figure 7(b), the electrode potential increases gradually at first and then instantaneously reaches to a much higher potential for all catalysts. This is due to the fact that during the chronopotentiometric experiment, the carbonaceous residues are accumulated on the surface of electrocatalysts, leaing to a lower electrocatalytic activity of catalysts [57]. Thus the potential must increase to satisfy the applied current until a potential is reached where larger amounts of H 2 O can be decomposed [58].…”
Section: Resultsmentioning
confidence: 99%